Pengaruh Disiplin terhadap Kinerja Pegawai pada Bagian Protokol dan Komunikasi Pimpinan Sekretariat Daerah Kabupaten Paser - Ernawati Ernawati; Abdul Rahim; Nur Alam; Lili Indah Agustina; Yotam Yotam; Muhammad Aliyafie (Pusat Riset dan Inovasi Nasional, 2025)
The purpose of this study was to determine the effect of discipline on employee performance in the protocol and communication section of the Paser Regency Regional Secretariat. The research method used in this study is a quantitative method. The population in this study were all employees working in the Protocol and Communication Section of the Paser Regency Regional Secretariat, totaling 34 people. In this study, the researcher used a total sample technique so that the sample in this study was 34 employees. The data analysis technique used was multiple linear regression analysis with the help of SPSS Version 26. The results of the study showed that the variables Preventive Discipline, Corrective Discipline, and Progressive Discipline had a positive effect on Employee Performance in the Protocol and Communication Section of the Paser Regency Regional Secretariat. Simultaneous testing of the F count value of 6.236 with a significance level of 0.002, it is known that the F table value is 2.92 (df 3:30) then 6.236> 2.92 means that together the discipline variables consisting of Preventive Discipline (X1), Corrective Discipline (X2), Progressive Discipline (X3), have an effect on Employee Performance (Y). From the results of the determination coefficient (R2) the Adjusted R Square value is 0.332 or 33.2% meaning that the independent variable, namely discipline (X) consisting of Preventive Discipline (X1), Corrective Discipline (X2), Progressive Discipline (X3), contributes 33.2% to Employee Performance, the remaining 56.8% is distributed by other variables not examined in this study.